The effect of e-cigarette and a conventional cigarette to the alveolus on Wistar male rats - Budian Nurpangestu; Yusrotun Kharimah; Fita Linggasati; Moch Bahrudin (International Journal of Advances in Applied Sciences, 2019)
Smoking can cause a variety of diseases one of them on pulmonary organs, e-cigarettes are also considered to be safer than conventional cigarettes and the number of smokers in Indonesia is increasing every year. The purpose of this study to determine differences in pulmonary alveolar damage in male rats (Rattus norvegicus Wistar strain) on electric cigarette smoke exposure and conventional cigarettes. This research is true experimental with post-test only control group design. Male rats were used as many as 25 rats were divided into 5 groups, namely the group P0 as a negative control group; P1 group was exposed to clove cigarettes; P2 group is exposed to a filter cigarette; P3 group was exposed to e-cigarette 0mg; P4 group exposed the e-cigarette 3mg. Samples were treated for 30 days. Data were analyzed using Kruskal Wallis with p <0.05. The results showed that there were significant differences in alveolar damage in the fifth group (p = 0.003). With Mann Whitney shows that groups P1, P2, P3, and P4 there are no significant differences. The conclusion of this study is there is no difference in alveolar damage on Wistar male rats by e-cigarettes and conventional cigarettes exposure.